Analisis Perputaran Piutang Terhadap Pelayanan Dan Return On Assets Pada Koperasi Produsen Tempe Tahu Indonesia Kabupaten Kuningan - khsan, Sugiyanto; Hidayat , Udin (Coopetition : Jurnal Ilmiah Manajemen, 2025)
The purpose of the study was to determine how the influence of receivables turnover on return on assets and services. In addition, to determine what efforts can be made to increase the return on assets of cooperatives. The method used in this study is a descriptive method with a quantitative approach. The results of this study indicate that receivables turnover in two soybean trading units and savings and loan business units is related to return on assets. Meanwhile, receivables turnover in the soybean trading business unit has no relationship with the service of the trading business unit and receivables turnover in the savings and loan business unit is related to the service of the savings and loan business unit. Keywords: Accounts Receivable Turnover, Return on Assets, Service, Cooperative